Direct and derivative shareholder suits : towards a functional and practical taxonomy - Koh, Alan K. (2022)
Shareholder litigation is an indispensable part of corporate law and governance. There is no shortage of excellent legal scholarship on various aspects of shareholder litigation from a comparative and functional perspective. Well-executed scholarly writing on comparative shareholder litigation can be informative and even enlightening for students and scholars of comparative corporate law. The goal of this chapter is to offer a taxonomy of shareholder litigation mechanisms informed by considerations relevant to a minority shareholder’s decision whether and how to proceed with a lawsuit. The central questions guiding the exposition below are these: What substantive outcomes are possible for a minority shareholder litigant, and which of these can each mechanism be used to achieve? This chapter proceeds as follows. Section 2 sets out four key considerations relevant to litigators that shape our discussion in subsequent parts. Section 3 classifies direct shareholder litigation mechanisms functionally according to whether the desired outcome is a monetary or non-monetary one. Section 4 addresses derivative litigation. Section 5 concludes.